A historical review of performance appraisal of public hospitals in China from the perspective of historical institutionalism - Li, Yaqing; He, Wensheng; Yang, Li; Zheng, Keshuang (Frontiers in Public Health, 2022)
The government performance appraisal of public hospitals serves as an effective management tool to promote high-quality development. It is also an important means of realizing the “Healthy China” initiative. Since the founding of the People's Republic of China, changes in performance appraisal have been divided into the following four periods: the early stage of performance appraisal (1949–1977), the exploration period (1978–2008), the development period (2009–2018), and the integration period (2019–present). This clarifies the regional practice of public hospital performance and identifies the institutional factors of the evolution. It also demonstrates that administrative forces, market-driving forces, and mission-driving forces combine to bring about change in the public hospital performance appraisal system. However, problems such as insufficient application of performance appraisal and coordination between health administrative departments and medical insurance departments still loom large.